PEMBANGUNAN DAN PEMBERDAYAAN MANUSIA MELALUI DANA DESA: POLA DARI MASA LALU HINGGA SINERGITAS YANG RANCU - Ashadi Cahyadi (JURNAL ILMIAH SYI'AR, 2019)
Nawa Cita requires the village as the core of development. Funds are rolled out for each village to support the development, empowerment, and welfare of some village subjects. The main assumption is that the synergy of infrastructure followed by community empowerment will produce sustainable welfare. This rationality is considered not running together because it provides a large portion of the infrastructure and understates human empowerment. This study tried to discuss village funds by reviewing past development patterns, community development, and correcting infrastructure-based development. The discussion in this paper has been supported by various journals, figures, and news from online media. All materials are read interactively, reduced, then the essence of reading is developed according to inductive reasoning. It was found that from the past, village programs always referred to the provisions of the central government. Even though the problems and needs of each village are very different. Then, the lack of understanding of the village apparatus about the program, it is not uncommon for programs to be rolled out to be replicas from other villages. This paper also discusses community-based development as a solution to village fund problems.